123k views
4 votes
Simplify the expression.


(6)/(1+√(3) )

1 Answer

5 votes

Answer:

Explanation:

Rationalize the denominator by multiplying both denominator & numerator by the conjugate of the denominator.

Conjugate of the denominator 1 + √3 is 1 - √3


(6)/(1+√(3))=(6(1-√(3)))/((1+√(3))(1-√(3)))\\\\=(6(1-√(3)))/((1+√(3))(1-√(3)))\\\\=(6(1-√(3)))/(1^(2)-(√(3))^(2))\\\\=(6(1-√(3)))/(1-3)\\\\=(6(1-√(3)))/(-2)\\\\=(-3)(1-√(3))\\\\=-3+3√(3)

User Jose A
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.